Self-healing nanocoatings - Trentin, Andressa [UNESP]; Uvida, Mayara Carla [UNESP]; de Araújo Almeida, Adriana [UNESP]; de Souza, Thiago Augusto Carneiro [UNESP]; Hammer, Peter [UNESP] (Elsevier, 2022)
The current demand of the automotive industry for durable high-performance paints with self-healing ability and environmental compatibility has prompted the research for the next-generation coatings. To accomplish extended durability, the development of smart coatings has been pursued, aiming to provide active protection after a corrosive or mechanical failure. Different approaches are used for developing smart/self-healing coatings, such as the addition of micro/nanocapsules containing organic or inorganic healing agents, vascular or shape memory polymers, polymers with reversible covalent bonds, and self-healing agents based on organic and inorganic compounds. The latter strategy, in particular, presents an excellent cost-benefit and low complexity, making this approach very promising for applications in the automotive industry. In this chapter, we give an overview of the state of the art of high-performance coatings, with particular emphasis on the smart inhibition mechanisms in different coating systems, providing the reader with an update on emerging self-healing technologies.
Keywords: Anti-corrosion coatings; Corrosion inhibitors; Functional nanocomposites; Organic-inorganic hybrids; Self-healing; Smart coatings